Reorientation of Islamic History Education: Integration of Critical Narratives, Values, and Civilizational Projection (A Systematic Literature Review) - Basyar, Syarifudin (Jurnal Intelek Insan Cendikia, 2025)
This systematic literature review research aims to comprehensively analyze the direction of development of Islamic History Education (IHE) in Indonesia through the integration of three fundamental dimensions: narrative, values, and civilization. The method used is the Systematic Literature Review (SLR) with the PRISMA protocol, analyzing 35 articles from SINTA and Scopus indexed journals published between 2019 and 2024. The findings reveal a significant paradigmatic shift. First, in the narrative dimension, there is a deconstruction of factual-chronological and political-dynastic narratives towards critical-hermeneutic, socio-cultural-intellectual, and multiperspective narratives. Second, in the value dimension, transformation occurs from a doctrinal transmission approach to a critical-constructive approach through ethical dilemma analysis and contextual reflection. Third, in the civilization dimension, orientation moves from romantic nostalgia towards critical-projective models that emphasize IHE as a laboratory for social analysis and a source of inspiration for civilizational projects. The main challenges to integration include the hegemony of mono-perspective textbooks, limited teacher pedagogical competence, epistemological tensions between positivism and normativism, and socio-political pressure from identity groups. This study concludes that an effective IHE model must be built on dialectical synergy between the three dimensions using participatory, problem-based, and project-based pedagogical approaches. Practical implications are directed at curriculum developers, textbook writers, educational policymakers, teacher training institutions, and further researchers.